Randki w ciemno - Steel, Danielle; Andrzejewska, Maria Karolina (Katowice : Wydawn. Ksiaznica, 2003)
Polish translation of "Dating Game". A humorous love story about dating customs after a divorce.
Translation of: Dating game.
Keywords: Dating (Social customs) -- Fiction; Divorced women -- Fiction; San Francisco (Calif.) -- Fiction